2020
DOI: 10.1002/pip.3370
|View full text |Cite
|
Sign up to set email alerts
|

Comparative degradation analysis of different photovoltaic technologies on experimentally simulated water bodies and estimation of evaporation loss reduction

Abstract: Degradation of photovoltaic (PV) systems on water bodies can be matter of serious concern due to high humid environmental conditions above water surface as compared with land surface. The primary objective of this study is to assess the reliability of various PV technologies for megawatt‐scale installations by analyzing their degradation on water bodies. An experimental study has been performed for 13 months on three commercially available PV technologies, namely, multicrystalline‐Si (m‐Si), heterojunction int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 61 publications
(69 reference statements)
1
14
0
Order By: Relevance
“…54 For certain cases, the performance of a SDM is found to be satisfactory, even after neglecting recombination losses existing in the diode. 55 However, for accurate curve reproduction, inclusion of recombination losses is helpful hence lead to the development of DDMs. 4 Further, inclusion of another diode improved its modeling performance and accuracy even at low irradiance conditions but at the cost of increased complexity.…”
Section: Modeling Methods Of Solar Pvmentioning
confidence: 99%
“…54 For certain cases, the performance of a SDM is found to be satisfactory, even after neglecting recombination losses existing in the diode. 55 However, for accurate curve reproduction, inclusion of recombination losses is helpful hence lead to the development of DDMs. 4 Further, inclusion of another diode improved its modeling performance and accuracy even at low irradiance conditions but at the cost of increased complexity.…”
Section: Modeling Methods Of Solar Pvmentioning
confidence: 99%
“…Figure 6 shows the variation of different solar cells’ relative spectral response and solar intensity (AM 1.5) with wavelength [36,37] . According to recent research focused on the degradation levels of solar cells, both HIT and CdTe have shown their suitability to be implemented in FPV plants in comparison with silicon solar cells [38,39] . This article, however, will concentrate on silicon solar cells due to their widespread use.…”
Section: Floating Pv Componentsmentioning
confidence: 99%
“…Over-canal systems are more humid environments than ground-mounted systems, thus it is possible that the over-canal PV panels could have increased reliability problems 45 . In tropical conditions the water content in the encapsulant may exceed the solubility which can lead to the formation of droplets of water in the modules that sometimes causes corrosion or other problems 46 .…”
Section: Assumptions and Uncertaintiesmentioning
confidence: 99%
“…Jordan and Kurtz (2013) reported degradation rates between 0-1%/year (over a two-year period) for a CdTe system installed in a tropical region (lower Morelos, Mexico) 47 . Kumar et al (2020) reported that CdTe technologies may be suitable for deployment on water bodies in subtropical humid environments because, over a oneyear period, there was only a marginal increase in the degradation rate of PV panels over water tanks compared with ground-mounted systems. Although reliability problems are unlikely in California's Central Valley because the relative humidity is lower during the warmest months of the year compared to Miami, FL, USA-a benchmark location for hot and humid conditions (Supplementary Fig.…”
Section: Assumptions and Uncertaintiesmentioning
confidence: 99%